Long-Lived Plasma Cells in Mice and Men - Brynjolfsson, Siggeir F.; Persson Berg, Linn; Olsen Ekerhult, Teresa; Rimkute, Inga; Wick, Mary-Jo; Mårtensson, Inga-Lill; Grimsholm, Ola (Frontiers in Immunology, 2018)
Even though more than 30 years have passed since the eradication of smallpox, high titers of smallpox-specific antibodies are still detected in the blood of subjects vaccinated in childhood. In fact, smallpox-specific antibody levels are maintained in serum for more than 70 years. The generation of life-long immunity against infectious diseases such as smallpox and measles has been thoroughly documented. Although the mechanisms behind high persisting antibody titers in the absence of the causative agent are still unclear, long lived plasma cells (LLPCs) play an important role. Most of the current knowledge on LLPCs is based on experiments performed in mouse models, although the amount of data derived from human studies is increasing. As the results from mouse models are often directly extrapolated to humans, it is important to keep in mind that there are differences. These are not only the obvious such as the life span but there are also anatomical differences, for instance the adiposity of the bone marrow where LLPCs reside. Whether these differences have an effect on the function of the immune system, and in particular on LLPCs, are still unknown. In this review, we will briefly discuss current knowledge of LLPCs, comparing mice and humans.